Strategies for Overcoming Barriers to Knowledge Sharing Between Headquarters and Subsidiaries Abroad - Sitar, Aleša Saša; Mihelič, Katarina Katja (Naše gospodarstvo/Our economy, 2014)
Employees encounter several barriers to knowledge sharing in organizational settings. Barriers can be classified as individual or organizational. Multinational corporations usually encounter additional barriers related to time differences and geographic distance as well as language and cultural differences. The authors of this paper first define knowledge sharing, addressing barriers to knowledge sharing and focusing specifically on barriers when knowledge is shared between headquarters and subsidiaries abroad. Second, approaches to overcoming those barriers are explained in detail. Finally, in the empirical part, based on semi-structured interviews with managers of three Slovenian companies with subsidiaries abroad, barriers and approaches to overcoming barriers to knowledge sharing are presented.